Evaluation of the Effectiveness of Local Food-Based Supplementation (Pemberian Makanan Tambahan) in Improving the Nutritional Status of Underweight Children under Five at a Public Health Center - Christiyanti, Ni Ketut Wenny; Janendra, Putu Sathiya Adi; Dwijayantari, Si Ayu Dinda; Purnami, Kadek Ima (Bali Medical and Wellness Journal, 2025)
Background: Malnutrition in children under five is a major public health concern in Indonesia. The government’s Supplementary Feeding Program or Pemberian Makanan Tambahan (PMT) aims to improve nutritional status, but its effectiveness needs further evaluation, especially in areas with persistent undernutrition. Aim: This study aimed to evaluate the effectiveness of the local PMT intervention in improving the nutritional status of undernourished children under five years old. Methods: An experimental one-group pre- and post-test design with a cross-sectional approach was used. The Wilcoxon Signed Rank Test facilitated statistical analysis. The study involved a total sample of 50 respondents who received locally sourced supplementary food over 60 days. Results: The study included 50 respondents, with a majority being male (26 toddlers, 52%) and female (24 toddlers, 48%). The findings revealed a statistically significant improvement (p <0.001) in the children's nutritional status, demonstrating the positive impact of the PMT intervention. Conclusion: Although the PMT program effectively enhanced nutritional status, its success is influenced by factors like adherence to dietary guidelines, parental involvement, and education. Integrating nutrition education and regular health monitoring is crucial to sustain long-term nutritional improvements in children.